PENGARUH FAKTOR DEMOGRAFI DAN IKLIM ORGANISASI TERHADAP NIAT WHISTLEBLOWING INTERNAL - Priyastiwi Priyastiwi (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2017)
This study aimed to examine the effect of demographic factors and organizational climate on the intention of internal whistleblowing. The sample was an accountant who had worked as an auditor. Data collection methods using questionnaires with financial statement fraud case scenarios. This research use ANOVA data analysis method to examine demographic factors include age, gender, and experience, as well as organizational climate on the intention of internal whistleblowing. The results showed only the experience of demographic factors that influence internal whistleblowing. Besides internal whistlelowing also influenced by organizational climate in the company.